Nueva especie gipsícola de Pinguicula (Lentibulariaceae) del estado de Oaxaca, México - Zamudio Ruiz, Sergio; Studnicka, Miloslav (Instituto de Ecología, A.C., 2000)
Pinguicula medusina, inhabitant of gypsum hills near Santiago Juxtlahuaca, Oaxaca, is described as a new species. Because of its subisolobe corolla with cylindrical tube and short spur, it is placed in the subgenus Isoloba, section Heterophyllum. This new taxon is closely related to P. heterophylla Benth. in its long linear “summer leaves”, but differs in the form and position of the corolla lobes, in the production of vegetative buds in the leaf apex and in its adaptation to grow on gypsum soils.